Emotional geographies and identity construction of Indonesian pre-service English teachers in a teaching practicum - Nur Arifah Drajati; Gary Barkhuizen; Agustina Tyarakanita; Kristian Adi Putra (Studies in English Language and Education, 2026)
This study explores how the emotional geographies of six Indonesian pre-service teachers (PSTs) during their teaching practicum experiences shaped their teacher identities and influenced their future career aspirations. This study employed a multimodal narrative inquiry approach, using drawings, photographs, and in-depth narrative interviews with the PSTs after the practicum. In the interviews, the PSTs were asked what the drawings meant to them, how they saw themselves as developing teachers, what their drawings meant, and how they felt about being and becoming teachers. The visual and textual data found in this study were subsequently analyzed using multimodal thematic analysis. This analysis aimed to understand the teachers’ practicum and imagined future teaching experiences, and to critically reflect on these events. The findings showed how the PSTs reflected on the dimensions of their emotional geographies, contributing to their identity construction and future career decisions. Teaching practicum served as a site for prospective teachers’ identity formation, and the emotions formed during classroom learning influenced how PSTs viewed themselves as educators. The teaching practicum also served as a concrete platform for identity formation, with emotional experiences closely intertwined with professional learning. This study demonstrates the need to address the development of teacher emotions as part of teacher identity construction. Implications for supporting PSTs emotionally and professionally, as well as directions for further research, are also discussed.